1997
DOI: 10.1159/000016424
|View full text |Cite
|
Sign up to set email alerts
|

Caries Development from 11 to 22 Years of Age: A Prospective Radiographic StudyPrevalence and Distribution

Abstract: The aim was to assess the distribution and pattern of caries development longitudinally in teenagers and adolescents whose treatment had been based on remineralizing rather than restorative strategies. A baseline cohort of 536 children was studied, using bite-wing radiographs, from 11 to 22 years of age. The results showed a slow but continuous increase in both enamel and dentin caries of approximal surfaces. At 21, 29% of all posterior approximal surfaces had enamel caries according to the radiographic diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
4
12

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(134 citation statements)
references
References 16 publications
11
107
4
12
Order By: Relevance
“…In particular, the system gives emphasis to the management of lesions that are disclosed through the bitewing radiographic survey during the clinical examination of patients. Approximal lesions demonstrated in bitewing radiographs are classified according to the following system: 16,17 C1: lesions in the outer half of enamel C2: lesions in the inner half of enamel C3: lesions just beyond the DEJ C4: lesions in the outer third of dentine C5: lesions in the inner two-thirds of dentine. Risk assessment, an important aspect of modern caries management, is necessary because the treatment protocols are risk-specific.…”
Section: The Caries Management Systemmentioning
confidence: 99%
“…In particular, the system gives emphasis to the management of lesions that are disclosed through the bitewing radiographic survey during the clinical examination of patients. Approximal lesions demonstrated in bitewing radiographs are classified according to the following system: 16,17 C1: lesions in the outer half of enamel C2: lesions in the inner half of enamel C3: lesions just beyond the DEJ C4: lesions in the outer third of dentine C5: lesions in the inner two-thirds of dentine. Risk assessment, an important aspect of modern caries management, is necessary because the treatment protocols are risk-specific.…”
Section: The Caries Management Systemmentioning
confidence: 99%
“…Nevertheless Hinds and Gregory 11 in England and Steckson-Blicks and Holm 37 in Sweden showed that the association between snacking and caries experience was only partially negated by the frequent use of fluoride toothpaste. Caries progressed through enamel and dentine in teenagers in a preventive programme which included a range of fluoride regimens 38 . In the two major studies of diet and caries, the use of fluoride toothpaste did not affect the relationship between sugar and caries 39,40 .…”
Section: The Interaction Of Sugars and Bacteriamentioning
confidence: 99%
“…The majority of approximal caries lesions in permanent teeth progress slowly, with an average lesion taking at least 3 years to progress through enamel to dentine. At levels of caries common in EU countries, the rates of progression of caries in people from 11 to 22 years is as follows: the median number of new approximal lesions per 100 tooth surface-years (there are 156 tooth surfaces per person) were 3.9 from no caries to caries halfway through enamel, 5.4, from halfway through enamel to spread into the outer half of dentine, and from broken enamel-dentine border to obvious spread in outer half of dentine, 20.3 38 . The DMFT increased from 3.2 at 12 years to 7.0 at 22 years.…”
Section: Some Epidemiological Characteristics About Caries ± the Natumentioning
confidence: 99%
“…Current evidence from epidemiological studies focusing on children, young adults, and adults have shown a shift in caries prevalence from occlusal surfaces at younger ages to approximal surfaces with advancing age (2)(3)(4)(5)(6)(7). Unlike the occlusal and free smooth surfaces, the approximal surfaces cannot be visualized directly due to the presence of neighboring teeth.…”
Section: Introductionmentioning
confidence: 99%